2008
DOI: 10.1186/gb-2008-9-10-r150
|View full text |Cite
|
Sign up to set email alerts
|

Distinct transcriptional MYCN/c-MYC activities are associated with spontaneous regression or malignant progression in neuroblastomas

Abstract: Background: Amplified MYCN oncogene resulting in deregulated MYCN transcriptional activity is observed in 20% of neuroblastomas and identifies a highly aggressive subtype. In MYCN single-copy neuroblastomas, elevated MYCN mRNA and protein levels are paradoxically associated with a more favorable clinical phenotype, including disseminated tumors that subsequently regress spontaneously (stage 4s-non-amplified). In this study, we asked whether distinct transcriptional MYCN or c-MYC activities are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
233
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(270 citation statements)
references
References 49 publications
26
233
1
Order By: Relevance
“…This additional separation suggests that MYCN/c-MYC signaling rather than MYCN levels alone underlies the differential expression of this miRNA signature. Indeed, c-MYC expression is Figure S2), confirming the inverse relationship between MYCN and c-MYC (Vandesompele et al, 2003), and has been shown to drive MYCN/c-MYC mRNA target gene expression in these tumors (Westermann et al, 2008). In addition, other genetic factors than increased MYCN/c-MYC activity could also contribute to the observed miRNA expression differences.…”
Section: Mycn/c-myc Microrna Signature Delineationsupporting
confidence: 61%
See 3 more Smart Citations
“…This additional separation suggests that MYCN/c-MYC signaling rather than MYCN levels alone underlies the differential expression of this miRNA signature. Indeed, c-MYC expression is Figure S2), confirming the inverse relationship between MYCN and c-MYC (Vandesompele et al, 2003), and has been shown to drive MYCN/c-MYC mRNA target gene expression in these tumors (Westermann et al, 2008). In addition, other genetic factors than increased MYCN/c-MYC activity could also contribute to the observed miRNA expression differences.…”
Section: Mycn/c-myc Microrna Signature Delineationsupporting
confidence: 61%
“…Patients in the first quartile, representing tumors with the lowest expression of predicted 8mer miRNA targets, have a particular poor prognosis as compared with those in the fourth quartile. Of interest, 48% of the tumors in the first quartile (n ¼ 66) were MYCN single-copy confirming that MYCN/c-MYC signaling rather than MYCN amplification underlies the poor outcome of these patients (Fredlund et al, 2008;Westermann et al, 2008). Moreover, 8mer miRNA-mediated target repression but not MYCN amplification status was an independent factor in a multivariate Cox regression model for EFS and OS (Supplementary Table S3).…”
Section: Mycn/c-myc-activated Micrornas Act In Concertmentioning
confidence: 83%
See 2 more Smart Citations
“…Based on the observation that stage 4S NB with higher levels of N-Myc proteins are more prone to spontaneous regression by apoptosis [35] or neuronal differentiation [36], it has been speculated that MYCN not only mediates malignant progression, but is also involved in spontaneous regression in favorable NB [37]. We, and others, have demonstrated that inhibition of MYCN leads to MYC upregulation [38]. For all these reasons, both MYC family members have to be simultaneously targeted.…”
Section: Twist1 Targeted Therapymentioning
confidence: 99%